Integrated IoT System for Real-Time Electrical Load Monitoring - Prasetyo, Yuli; Triwijaya, Santi; Khakim, Ainul; Prakoso, Dimas Nur; Winarno, Basuki (Journal Geuthee of Engineering and Energy, 2025)
The uncontrolled and excessive consumption of electrical energy, especially in households, often leads to significant energy waste. This issue adversely affects both consumers and electricity providers such as PLN. To address this problem, a system titled "Centralized Monitoring and Control Based on Load Characteristics Using the Internet of Things (IoT)" was developed. This system is designed to monitor and control household electrical loads in real time. The system consists of a PZEM-004T sensor for measuring voltage, current, power, energy usage, frequency, and power factor. An Arduino microcontroller processes the sensor data, while an ESP32 module transmits the data to an online database. A relay module is used to control electrical devices remotely. The data is stored in a database and visualized through a web-based interface, which also enables users to download monitoring reports in PDF or Excel formats. Testing results showed that the system operates with high accuracy. When compared to a standard power analyzer, the measurement error for parameters such as voltage, current, frequency, and power factor remained low, with a maximum error of only 1.9%. It demonstrates the system’s potential for efficient energy monitoring and management in residential settings.